Monitoring the reaction and response of people to urban noise - Diana Ioana POPESCU; Iuliana Fabiola MOHOLEA (Archives of Acoustics)
An important aspect in assessing noise in urban agglomerations is the subjective one, which takes into account the sensitivity and specific reactions of residents to the noise in their living environment. This paper presents results of a sociological study initiated to determine the population awareness, regarding the urban acoustic environment and estimation of effects and disturbance. The survey was conducted in a Romanian city, to complement the information provided by the strategic noise map of the area. This approach allows the estimation of specific local patterns of reaction and response to urban noise of the exposed population and provides the information, needed to develop action plans and to set proper solutions for urban area planning.